The Efficiency of the Song Repertoire on the Musical Development Level of Pre-School Children Aged Six Years Old - GÜL, Gülnihal; BOZKAYA, İsmail (My University, 2017)
In this research it was aimed to form a nursery rhymes repertoire for preschool children, which is appropriate for the necessities of the Early Childhood Education Program and to help pre-school music teachers carry out more efficient and productive work. Towards this aim, a song repertoire was formed by the researcher, experimental and control groups were specified and work was carried out with the experimental group for 12 weeks. A pre-test and a final test were applied to the experimental and control groups before and after practice with the use of a “musical skills measuring device” prepared by the researcher and statistical analyzed of the obtained data were performed. According to the data gained from the research results, it was stated that the activities performed in music education created a positive effect on the musical development of 6 year old children.
Okul Öncesi Altı Yaş Çocukları İçin Oluşturulan Şarkı Dağarcığının Müziksel Gelişim Düzeylerine Etkisi
Bu araştırmada ana sınıfı öğrencileri için Okul Öncesi Programı gereklerine uygun çocuk şarkıları dağarcığı oluşturmak, okul öncesi düzeyde müzik eğitimi veren öğretmenlerin daha etkili ve verimli çalışmalar yapmasına katkı sağlamak amaçlanmıştır. Bu amaç doğrultusunda, araştırmacı tarafından şarkı dağarcığı oluşturulmuş, deney ve kontrol grupları belirlenerek deney grubu ile 12 hafta çalışılmıştır. Uygulama öncesi ve sonrasında deney ve kontrol grubuna araştırmacı tarafından hazırlanan “müziksel beceri ölçme aracı” kullanılarak ön test ve son test uygulaması yapılmış ve elde edilen verilerin istatistiksel çözümlemeleri yapılmıştır. Araştırma sonuçlarından elde edilen verilere göre, araştırmacının hazırlayıp uyguladığı şarkı dağarcığı ile gerçekleştirilen müzik eğitimi etkinliklerinin; 6 yaş grubu çocukların müziksel gelişim düzeyleri üzerinde olumlu etki yarattığı görülmüştür.
Keywords: Preschool education, music education, song repertoire